Comprehensive analysis of inhibitory checkpoint ligand expression by glioblastoma cells. Issue 4 (28th December 2020) - Robilliard, Laverne D; Yu, Jane; Anchan, Akshata; Joseph, Wayne; Finlay, Graeme; Angel, Catherine E; Scott Graham, E
Abstract: Glioblastoma is a highly aggressive brain malignancy commonly refractory to classical and novel chemo‐, radio‐ and immunotherapies, with median survival times of ~15 months following diagnosis. Poor immunological responses exemplified by the downregulation of T‐cell activity, and upregulation of immunosuppressive cells within the tumor microenvironment have limited the effectiveness of immunotherapy in glioblastoma to date. Here we show that glioblastoma cells express a large repertoire of inhibitory checkpoint ligands known to control effector T cell responses. Furthermore, flow cytometry analysis reveals that glioblastoma cells with an enhanced stem cell‐like phenotype express several investigated ligands at significant levels on their cell surface. This reveals that glioblastoma stem‐like cells express suppressive ligands with the potential of suppressing major T cell checkpoint receptors. With this information, it is now essential that we understand the relevance of this extensive repertoire of immune checkpoint ligands and their functional consequence on immune evasion in glioblastoma. This is necessary to develop effective immunotherapeutics and to be able to match treatment to patient, especially in the light of CheckMate 143. Abstract : Human glioblastoma stem cells express a broad range of suppressive immune checkpoint ligands. This paper shows the most comprehensive analysis of this expression that has been conducted. These data have significant implications for clinical trials in glioblastoma relating to any immunotherapy strategies.